Distributed public service broadcasting as an alternative model for public service broadcasting in South Africa - Pieter Jacobus Fourie (Communicare)
The purpose of this article is to propose/justify a new model for South African public service broadcasting, namely, distributed public service broadcasting. The justification is done against the background of a description of the changed and converged new media environment brought about by technological developments with the concomitant new production, content and distribution challenges and with interactivity as the new foundation of communicator-audience relationships. It is argued that the new media environment requires new thinking about public service broadcasting (PSB). The need for a new model is further justified against the background of the continued governance, managerial and financial problems the South African Broadcasting Corporation (SABC) has been experiencing for more than a decade, which has led to a new but controversial Public Service Broadcasting Bill (2009/2010) in an attempt to address the problems. It is argued that the problems will not be resolved. Instead, a new broadcasting model should rather be considered. It should, however, be emphasised that distributed public service broadcasting as a new model is only introduced in this article. Detail about the model is the topic of additional research that has yet to be done. Finally, the article should be read against the background of what were, at the time of writing in 2010, a number of serious governmental threats to freedom of expression with government proposing, inter alia, the introduction of a controversial Bill on the Protection of Information and also of a Media Appeals Tribunal – both of these constituting further threats to the autonomy of the public broadcaster and which makes it even more urgent that a new broadcasting model be considered. The above topics are addressed in separate parts of the article dealing with context, problems besetting South African public service broadcasting, past and present efforts to address the problems, a justification for a new model – one focusing on the new converged and digitised media environment – new thinking about regulation, the changed nature of social responsibility, a semiotic justification,